Queen Victoria: Gender and Power - Elliott, Bridget (Labour / Le Travail, 1991)
The article reviews the book, "Queen Victoria: Gender and Power," by Dorothy Thompson.
Keywords: BOOKS -- Reviews; Nonfiction; QUEEN Victoria: Gender & Power (Book); THOMPSON, Dorothy, 1923-2011; WOMEN in politics